(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Extraordinary changes caused by COVID-19 have enforced companies around the globe to accelerate transition to digital business processes. Human resource management (HRM) is in the heart of these transformations helping organizations to navigate in the vague present and unforeseeable future. HRM needs to manage people in companies during the crisis in order to enable business continuity and ensure work-life balance. Since the future will bring more flexible, remote-friendly, digital working norms, the changes in policies, processes, workspaces, collaboration systems, and employee wellness are of increasingly urgent importance. The paper discusses the challenges HRM is facing due to the current crisis in terms of remote working, and identifies the implications the pandemic has on human resources. The expert interviews conducted in Georgia indicate that HRM should consider ways to develop new policies for hybrid working models as a response to the current pandemic crisis.